A novel shell-and-tube heat exchanger design with alternative inclined baffles - Huy Minh Khoi Hoang; Hai-Lam Cao; Phuoc Minh Quang Pham; Ahmad Hajjar; Vu Linh Nguyen (Case Studies in Thermal Engineering)
This paper proposes a novel single-shell-pass shell-and-tube heat exchanger design with alternative inclined baffles. The design includes paired semi-ellipse shapes with baffle cut along the vertical axis such that the segments are interlocked in a crossed pattern. The new exchanger is structured to overcome the weakness of single segmental baffles (SG-STHX) by achieving lower pressure drop and higher thermal efficiency. This advantage is achieved using spiral flow to reduce dead zones and make the flow distribution within the heat exchanger's shell more uniform. The relatively simple arrangement and design of baffles in the proposed exchanger offer a significant advantage compared to continuous helical baffles (CH-STHX) in terms of the complexity of manufacturing and consequent high cost. In this paper, the equations governing the flow and thermal transfer in the exchanger are presented, and the parameters used to evaluate the exchanger's performance are also developed. The finite-volume method is used in numerical simulations to verify the equations and compare the performance of the novel design to SG-STHX and CH-STHX under similar geometrical and thermo-hydraulic conditions. Different mass flow rates are considered to cover a wide range of Reynolds numbers and ensure the accuracy of the comparison. Flow velocity and temperature distributions across the shell side are plotted to address the impact of geometry on the fluid behavior during the flow. The results show that the proposed heat exchanger significantly improves comprehensive performance, especially energy efficiency, compared to conventional SG-STHX or CH-STHX. The proposed heat exchanger also has a lower pressure drop than traditional ones. With the same mass flow rate, the XX-STHX demonstrates an average pressure drop approximately 44 % lower than the CH-STHX and 49 % lower than the SG-STHX. Moreover, with the same pump power, the performance evaluation factor of the XX-STHX, on average, surpasses that of the CH-STHX by roughly 1.48 times and the SG-STHX by about 1.70 times.